Feasibility of using asphaltites from Pesca Boyacá in flexible pavement structures - Alarcón Dallos, J.; Galvis Pinzón, W.; Suarez Rivera, P. (Revista Ingeniería de Construcción, 2023)
The use of unconventional materials has been a widely studied and used technique around the world. The results of the comparative analysis of a dense cold mix of aggregates with the addition of asphaltite from a technical and economic point of view is reported. The study was carried out using the methods developed by Marshall and Ramcodes, which characterized the aggregates first, in order to make an accurate comparison between the specifications and volumetric properties obtained and determine if asphaltite can be used in the construction of layers of flexible pavements in Colombia. The mix designed for the gradation of the central limit of the specifications using asphaltite meets the design criteria for a cold dense mix used in patching work except for flow. These mixtures can have a better performance than conventional mixtures while remaining economic. The use of Pesca, Boyacá asphaltites as a fine aggregate in a dense cold mix with asphalt emulsion is promising. This is due to its increased stability at an initial manufacturing cost which is lower than the cost of a conventional mix.